Extensive and Potential Life-Threatening Bilateral Neck Swelling Post-Tonsillectomy: A Case Report - Mohammed, Mohammed A Elkrim S.; Hussain, Syed Zohaib Maroof; Yousif, Mohammed (Archives of Clinical and Medical Case Reports, 2026)
Objective: This paper reports an unusual case of post-tonsillectomy emphysema and pneumomediastinum. Methods: This is a clinical case report with a review of literature. Results: Tonsillectomy is one of the most common otolaryngological procedures. It is a safe procedure, however, there are some complications typically associated with tonsillectomy. A 28-year-old female presented with a less than one-day history of extensive right-sided tender neck swelling. The patient underwent bilateral tonsillectomy, which was uneventful, but subsequently developed a sudden onset of right-sided neck swelling on the zero-post-operative day. Extensive crepitus was felt on palpation. Examination findings were confirmed by imaging. The patient was conservatively managed and subsequently discharged home. Conclusion: Post-tonsillectomy surgical emphysema and pneumomedia stinum are rare complications. Pneumomediastinum and bilateral neck involvement made our case rather unique. Surgical technique plays an important role, especially in the adhesions of tissues. Patients should be managed conservatively under close observation. Avoidance of coughing and straining will help to prevent the worsening.